Dendritic Cells Pulsed with Tumor Lysates Induced by Tetracyanotetra(aryl)porphyrazines-Based Photodynamic Therapy Effectively Trigger Anti-Tumor Immunity in an Orthotopic Mouse Glioma Model - Tikhon S. Redkin; Ekaterina E. Sleptsova; Victoria D. Turubanova; Mariia O. Saviuk; Svetlana A. Lermontova; Larisa G. Klapshina; Nina N. Peskova; Irina V. Balalaeva; Olga Krysko; Tatiana A. Mishchenko; Maria V. Vedunova; Dmitri V. Krysko (MDPI AG, 2023)
Research in the past decade on immunogenic cell death (ICD) has shown that the immunogenicity of dying tumor cells is crucial for effective anticancer therapy. ICD induction leads to the emission of specific damage-associated molecular patterns (DAMPs), which act as danger signals and as adjuvants to activate specific anti-tumor immune responses, leading to the elimination of tumor cells and the formation of long-term immunological memory. ICD can be triggered by many anticancer treatment modalities, including photodynamic therapy (PDT). However, due to the variety of photosensitizers used and the lack of a universally adopted PDT protocol, there is a need to develop novel PDT with a proven ICD capability. In the present study, we characterized the abilities of two photoactive dyes to induce ICD in experimental glioma in vitro and in vivo. One dye was from the tetracyanotetra(aryl)porphyrazine group with 9-phenanthrenyl (pz I), and the other was from the 4-(4-fluorobenzyoxy)phenyl (pz III) group in the aryl frame of the macrocycle. We showed that after the photosensitizers penetrated into murine glioma GL261 cells, they localized predominantly in the Golgi apparatus and partially in the endoplasmic reticulum, providing efficient phototoxic activity against glioma GL261 cells upon light irradiation at a dose of 20 J/cm2 (λex 630 nm; 20 mW/cm2). We demonstrated that pz I-PDT and pz III-PDT can act as efficient ICD inducers when applied to glioma GL261 cells, facilitating the release of two crucial DAMPs (ATP and HMGB1). Moreover, glioma GL261 cells stimulated with pz I-PDT or pz III-PDT provided strong protection against tumor growth in a prophylactic subcutaneous glioma vaccination model. Finally, we showed that dendritic cell (DC) vaccines pulsed with the lysates of glioma GL261 cells pre-treated with pz-I-PDT or pz-III-PDT could act as effective inducers of adaptive anti-tumor immunity in an intracranial orthotopic glioma mouse model.